Hormonal treatment for endometriosis associated pelvic pain - Wu Shun Felix Wong; Chi Eung Danforn Lim (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2011)
AbstractBackground: Endometriosis is a common gynecological problem associated with chronic pelvic pain. Objective: To evaluate the effectiveness of current hormonal treatments of endometriosis associated pain.Materials and Methods: Randomized Controlled studies identified from databases of Medline and Cochrane Systemic Review groups were pooled. 7 RCTs were recruited for evaluation in this review. Data from these studies were pooled and meta-analysis was performed in three comparison groups: 1) Progestogen versus GnRHa; 2) Implanon versus Progestogen (injection); 3) Combined oral contraceptive pills versus placebo and progestogen. Response to treatment was measured as a reduction in pain score. Pain improvement was defined as improvement ≥1 at the end of treatment. Results: There was no significant difference between treatment groups of progestogen and GnRHa (RR: 0.036; CI:-0.030-0.102) for relieving endometriosis associated pelvic pain. Long acting progestogen (Implanon) and Mirena are not inferior to GnRHa and depot medroxy progesterone acetate (DMPA) (RR: 0.006; CI:-0.142-0.162). Combined oral contraceptive pills demonstrated effective treatment of relieving endometriosis associated pelvic pain when compared with placebo groups (RR:0.321CI-0.066-0.707). Progestogen was more effective than combined oral contraceptive pills in controlling dysmenorrhea (RR:-0.160; CI:-0.386-0.066), however, progestogen is associated with more side effects like spotting and bloating than the combined contraceptive pills. Conclusion: Combined oral contraceptive pills (COCP), GnRHa and progestogens are equally effective in relieving endometriosis associated pelvic pain. COCP and progestogens are relatively cheap and more suitable for long-term use as compared to GnRHa. Long-term RCT of medicated contraceptive devices like Mirena and Implanon are required to evaluate their long-term effects on relieving the endometriosis associated pelvic pain